AYURVEDIC MANAGEMENT OF GENERALISED ANXIETY DISORDER - A CASE REPORT (AYUSHDHARA, 2023)
Stress is a very common word that we hear in our custom. But when it becomes excessive, persistent and disruptive it becomes a trouble. Generalized anxiety disorder (GAD) is a common mental disorder that involves constant and chronic tension, worrying and nervousness. In India GAD has high prevalence of 5.8%. Compared to a panic attack, its intensity is less but chronicity is longer. GAD makes the person exhausted mentally and physically and makes problems emotionally and behaviorally affecting the quality of life badly because functional somatic symptoms in GAD shows a wide range. In Ayurveda, the symptoms of GAD shows characteristics of Chittodwega and indicates a very effective management.A 25 year old male attended in OPD with increased tension, fear and uncontrollable anxiety, disturbed sleep, and stomach ailments, constipation, belching and reduced appetite. On interrogation it was revealed that he developed the symptoms over the last 2 years. Mental status examination was done. Considering the signs and symptoms, he was diagnosed with GAD.Internally he was given with Somalatha Choorna, Aswagandharishta, Gokshura Choorna, Aswagandha Choorna and Sarpagandha Choorna to manage his anxiety and stomach ailments. Procedures done were Thala Pothichil, Snehapana, Virechana and Nasya to reduce his anxiety and other problems. During this time, he was also subjected to meditation and counselling techniques as well. The patient responded well to the treatment and his symptoms improved significantly. HAM-A scale score before treatment was 24 which was reduced to 6 after treatment. On discharge he was advised to continue the medicines and relaxation techniques. The Ayurveda protocol was found to be effective in managing GAD and highlights the importance of ayurvedic psychiatric treatments in similar conditions.